2015
DOI: 10.1186/s12985-015-0267-7
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B serologic survey and review of immunization records of children, adolescents and adults in Fiji, 2008–2009

Abstract: BackgroundIn Fiji, hepatitis B (HB) vaccine was introduced into childhood immunization program in 1989 and has been administered as a pentavalent since 2006. This study aimed to: (i) survey and examine the extent to which HB infection continue to occur in children, adolescents and adults in Fiji, and (ii) determine HB coverage rates and timeliness of vaccine administration to children.MethodsSerum samples of children, adolescents and adults (aged 6 months to <5 years, 16–20 years, and 21–49 years, respectively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 9 publications
0
11
0
Order By: Relevance
“…The prevalence of HBsAg in the corresponding no vaccination cohorts were substantially higher, ranging from 0.6% 48 to 16.3% 34 (median: 9.8%). All except one study 45 reported a decrease in HBsAg prevalence; the combined RP in vaccinated populations was 0.24 (95% CI: 0.16–0.35; Fig. 2 ).…”
Section: Resultsmentioning
confidence: 94%
See 4 more Smart Citations
“…The prevalence of HBsAg in the corresponding no vaccination cohorts were substantially higher, ranging from 0.6% 48 to 16.3% 34 (median: 9.8%). All except one study 45 reported a decrease in HBsAg prevalence; the combined RP in vaccinated populations was 0.24 (95% CI: 0.16–0.35; Fig. 2 ).…”
Section: Resultsmentioning
confidence: 94%
“…Restricting analyses to those with HBsAg prevalence under 10% in the unvaccinated group yielded 10 studies, all of which assessed HBsAg positivity in cohorts with universal vaccination. 29 , 30 , 36 40 , 45 , 47 , 48 The combined RP was 0.34 (95% CI: 0.23–0.52). In comparison, RP was 0.17 (95% CI: 0.12–0.25) across the 11 studies with HBsAg prevalence of at least 10% in the unvaccinated cohort.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations